Formation and variability of the South Pacific Sea Surface Salinity maximum in recent decades. Issue 10 (8th October 2013) - Hasson, Audrey; Delcroix, Thierry; Boutin, Jacqueline
<x xml:space="preserve">Abstract</x> [1] This study investigates causes for the formation and variability of the Sea Surface Salinity maximum (SSS > 36) centered near 18°S–124°W in the South Pacific Ocean over the 1990–2011 period at the seasonal time scale and above. We use two monthly gridded products of SSS based on in situ measurements, high‐resolution along‐track Voluntary Observing Ships thermo‐salinograph data, new SMOS satellite data, and a validated ocean general circulation model with no direct SSS relaxation. All products reveal a seasonal cycle of the location of the 36‐isohaline barycenter of about ±400 km in longitude in response to changes in the South Pacific Convergence Zone location and Easterly winds intensity. They also show a low frequency westward shift of the barycenter of 1400 km from the mid 1990s to the early 2010s that could not be linked to the El Nino Southern Oscillation phenomena. In the model, the processes maintaining the 22 year equilibrium of the high salinity in the mixed layer are the surface forcing (∼+0.73 pss/yr), the horizontal salinity advection (∼−0.37 pss/yr), and processes occurring at the mixed layer base (∼−0.35 pss/yr).